Impact Of Financial Performance on The Innovation and Development of Research and Development in Electric Vehicle Industry - El Gibran, Pangeran Alif; Nainggolan, Yunieta Anny (Masyarakat Ekonomi Syariah Bogor, 2025)
This thesis explores the relationship between financial performance and technology development decisions in Indonesian electric vehicle (EV) companies. The EV industry is crucial for Indonesia's sustainable transportation and environmental goals, but the country faces challenges such as limited infrastructure, high costs of adoption, and inconsistent government incentives. To address these issues, the research focuses on identifying the role of financial performance metrics, such as revenue growth, profit margins, cash flow, investment levels, and cost control, in influencing decisions related to technology development, innovation, and new product launches. The study employs a quantitative approach to examine the relationships between financial performance indicators and technology development outcomes. Secondary data will be collected from publicly available financial statements, company reports, and relevant industry databases of Indonesian EV manufacturers. Statistical tools, including regression analysis and correlation testing, will be used to identify patterns, relationships, and the significance of financial indicators in driving innovation and R&D investments. The findings will offer practical insights for policymakers, investors, and industry stakeholders. Policymakers can use the research outcomes to design targeted incentives and regulations that support innovation and financial growth. Investors will benefit from a clearer understanding of financial health indicators that influence technological progress, enabling better decision-making in EV-related investments. The research contributes to academic literature and industry practice by examining the financial-technology nexus within emerging markets, a domain often overlooked in favor of studies focused on developed economies. By addressing financial and policy barriers to innovation, the study supports Indonesia's broader goals of reducing carbon emissions, enhancing energy security, and fostering economic growth